Organizational Relationship with Improving the Quality of Services at the Baranti Health Center, Sidrap Regency - Muhammad Tahir; Sri Handayani; Asmah Sukarta (Universitas STRADA Indonesia, 2022)
Health services are health programs aimed at individuals or the community and implemented jointly within an organization and with the aim of maintaining or improving the level of health by improving the quality of services in accordance with service standards and professional standards with existing and available potential. The aim of this research is to analyze the relationship between organizations and improving the quality of services at the Baranti Health Center, Sidrap Regency in 2019. This research was carried out from 16 May to 14 June 2019 at the Baranti Health Center, Sidrap District. This research is a quantitative research with a cross sectional approach carried out in the working area of ​​the Baranti Community Health Center, Sidrap Regency. The sample size in this research was 51 respondents, using purposive sampling as a sampling technique. The results of the study using Chi-square analysis with a significant level (p = 0.001; p < 0.05) showed that there was a relationship between organization and improving the quality of Puskesmas services as many as (70.6%) of Puskesmas Puskesmas employees were active in organizations and had good quality improvements as many as (82.4%) at the Baranti Community Health Center, Sidrap Regency. There is a relationship between organization and improving the quality of service at the Baranti District Health Center, Sidrap Regency in 2019, as evidenced by the results of the Square P-Value test of 0.001 < 0.05.